Vocational Skills Program in Shaping The Independence of Children with Motoric Disabilities at SMALB Level - Nabila, Salwa; Afifah, Nawar; Khoeriah, N Dede (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The dual purpose of education for children with disabilities is related to the rehabilitation aspect of restoring and developing physical function, and related to education which refers to the objectives of national education which aims to develop the potential of students to become human beings who are faithful and devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. Frances P. Connor (1995) suggests that there are at least 7 aspects that need to be developed in each disabled child through education, namely: (1) intellectual and academic development, (2) physical development, (3) emotional development and self-acceptance, (4) social maturity, (5) moral and spiritual maturity, (6) self-expression, and (7) future preparation. Children with significant physical or motor limitations require a specialized approach in developing their independence. One effective approach is through the development of vocational skills. This article discusses the importance of vocational skills programs in enhancing the independence of children with motor impairments in the context of education and/or rehabilitation. Practical steps include identification of relevant vocational skills, development of an inclusive vocational skills program, appropriate training and mentoring, and integration with the education curriculum. The results show that vocational skills development helps children with disabilities become independent in daily life and preparation for the world of work, improves quality of life, and provides wider career opportunities. Implications and recommendations include inclusive curriculum development, teacher training, industry and community partnerships, and the use of technology in skills development. With a holistic and inclusive approach, vocational skills development for children with disabilities supports social inclusion and equitable community development.